Intellectual capital disclosure of Hungarian and Czech listed firms - Edit Lippai-Makra; Zsolt Rádóczi; Zsuzsanna Ilona Kovács (European Financial and Accounting Journal, 2019)
The purpose of this paper is to investigate the level of intellectual capital (IC) disclosure of the largest Czech and Hungarian listed firms. We apply content analysis of the annual statements and measure IC disclosure by a score. We hypothesize that a significant positive relationship exists between IC disclosure score and such firm-specific financial factors as company size, profitability, book value of intangibles and trade volume. The results of the regression model indicate that among the chosen independent variables, capitalized intangibles and profitability have a significant impact. Another contribution of the paper is the comparison of the two aforementioned Central European countries, which can serve as a basis for future research about the reporting culture of the region.
Keywords: M41; 650; intellectual capital; voluntary disclosure; content analysis